Anti-microbial sensitivity and resistance of organisms in blood-culture samples from prolonged fever cases: evidence from a tertiary care hospital in West Bengal, India - Ghosh, Somanjana; Lahiri, Arista; Bera, Siddhartha; Bandyopadhyay, Soumyajyoti (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Currently there is a rise in resistance to anti-microbials which is a matter of concern in treatment of systemic infections. Blood culture is considered “gold standard” in diagnosis of suspected systemic infection. The susceptibility to antibiotics thereafter determine the future course of treatment. The current study aims to find out the sensitivity and resistance pattern of the blood culture isolates. Methods: A cross-sectional study was performed on the blood culture samples sent within 24hours of admission of the adult patients reporting fever for 7 days or more with no history of consumption of any antibiotics within last month. Total 134 blood samples were analysed. The proportion of sensitivity and resistance to anti-bacterial agents was calculated among those samples which showed growth in the culture. Background information of the patients in terms of age, sex and religion were also noted. Results: Mean age of the patients was 39.33 (±12.19) years. Overall 47.76% were female patients and remaining were male. Among the Hindu patients majority were male while among Muslims majority were female. Of the total number of blood cultures examined 46.27% showed growth of bacteria. Staphylococcus aureus was the most frequently found bacteria isolated in cultures, followed by coagulase negative Staphylococcus and Pseudomonas. Of the frequently used antibiotics, higher sensitivity was seen with vancomycin, amikacin, netilmycin, imipenem, gentamicin. High resistance was observed in use of antibiotics like cefixime, amoxicillin-clavulanic acid and azithromycin. Conclusions: High level of resistance to several commonly used advanced antibiotics warrant judicial and evidence-based use of these drugs.